1990
DOI: 10.1007/bf00011118
|View full text |Cite
|
Sign up to set email alerts
|

15N estimates of nitrogen fixation by white clover (Trifolium repens L.) growing in a mixture with ryegrass (Lolium perenne L.)

Abstract: The 15N isotope dilution technique and the N difference method were used to estimate N 2 fixation by clover growing in a mixture with ryegrass, in a field experiment and a controlled environment experiment. Values obtained using N difference were approximately 25% lower than those estimated using 15N isotope dilution. In the field experiment there was a measured N benefit to grass growing with clover, equivalent to 42.7 kgN ha -1. The grass in the mixture had a lower atom %15N content and a higher N content th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 45 publications
4
19
1
1
Order By: Relevance
“…McNeil and Wood (1990), obtained similar results which may be explained by the fact that the 15 N isotope dilution technique integrates overtime the N derived from BNF hence masking seasonal variations. Pichard et al (1986), studied the influence of cutting frequency on the botanical composition of these prairies, and found that the increase in cutting frequency favoured a higher proportion of leguminous plants and, consequently, a higher protein value of the sward.…”
Section: Discussionsupporting
confidence: 84%
“…McNeil and Wood (1990), obtained similar results which may be explained by the fact that the 15 N isotope dilution technique integrates overtime the N derived from BNF hence masking seasonal variations. Pichard et al (1986), studied the influence of cutting frequency on the botanical composition of these prairies, and found that the increase in cutting frequency favoured a higher proportion of leguminous plants and, consequently, a higher protein value of the sward.…”
Section: Discussionsupporting
confidence: 84%
“…Consequently, fixed N was almost none in plots fertilized with 90 g m 22 year 21 N in the third production year. Averaged across 3 years, apparent N 2 fixation ranged from 37.7 to 39.0 g m 22 year 21 under unfertilized conditions and from 24.8 to 36.2 g m 22 year 21 when these species were fertilized with different levels of N. The N 2 fixation data are comparable with estimates of several researchers (Ledgard and Steele 1992;Whitehead 1995;McNeil and Wood 1990;Jorgensen, Jensen, and Schjoerring 1999), who reported annual amounts of N 2 fixation between 23 and 296 kg N ha 21 in different forage mixtures.…”
Section: N 2 Fixationsupporting
confidence: 69%
“…The quantity of N fixed by white clover in the mixtures can vary from none to about 400 kg N ha 21 year 21 , and productive mixtures often fix between 100 and 200 kg N ha 21 year 21 (Whitehead 1995). Nitrogen fixation by white clover in the U.K. was 155 kg N ha 21 ; about 28% of this was subsequently transferred to perennial ryegrass and accounted for 29% of the total N content of ryegrass (McNeil and Wood 1990). Jorgensen, Jensen, and Schjoerring (1999) indicated that the amounts of N fixed in the perennial ryegrass and white clover mixture were 23, 187, and 177 kg N ha 21 in the seeding, first, and second production year, respectively, whereas pure stand white clover fixed 28, 262, and 211 kg N ha 21 in the 3 years.…”
Section: Introductionmentioning
confidence: 99%
“…The transfer of atmospheric derived nitrogen appears to increase with time (Table 3; Heichel and Henjum, 1991;Ledgard et al, 1985b;Mallarino et al, 1990;McNeill and Wood, 1990;Merckx et al, 1985). In a young clover-grass system only small amounts of atmospheric derived nitrogen is expected to be transferred from clover to grass, since the transfer presumably takes place via the microbial biomass.…”
Section: Discussionmentioning
confidence: 99%